(untitled) (Global Journal of Science Frontier Research, 2018)
Jute and polybutylene have different characters in their properties. When they are blended, their blended composition shows various purposes. The goal of the research is to enhance the properties of jute fiber (JF) reinforced polybutylene (PB) composite. It was made by sample ho press molding method according to the weight percentage of 25 wt% filler (JF), 2wt% coupling agent (compatibilizer) degraded PB (DgPB) and maleated PB (MAPB) and 70 wt% matrix (PB). To improve the interfacial interactions between the fiber and PB, the fiber was chemically modified with 10w/v% NaOH, 6w/v% dicumyl peroxide (DCPO), 0.05 w/v% K2Cr2O7 and 5 w/v% H2O2 solution. The water absorption, tensile and thermal properties of raw and surface treated fibers composites were compared in particular coupling agent. It has found that the fiber treatments and the addition of coupling agents, composites showed better properties. Among the composites, 10 wt/v% NaOH treated jute reinforced PB composite by using MAPB compatibilizer was presented better water absorption and mechanical properties.